The Fate of Tau Aggregates Between Clearance and Transmission - Seitkazina, Assel; Kim, Kyu Hyeon; Fagan, Erin; Sung, Yoonsik; Kim, Yun Kyung; Lim, Sungsu (Frontiers in Aging Neuroscience, 2022)
Neuronal accumulation of misfolded tau is the pathological hallmark of multiple neurodegenerative disorders, including Alzheimer’s disease. Distinct from amyloid plaques, which appear simultaneously throughout the brain, tau pathology develops first in a specific brain region and then propagates to neuroanatomically connected brain regions, exacerbating the disease. Due to the implication in disease progression, prevention of tau transmission is recognized as an important therapeutic strategy that can halt disease progression in the brain. Recently, accumulating studies have demonstrated diverse cellular mechanisms associated with cell-to-cell transmission of tau. Once transmitted, misfolded tau species act as a prion-like seed for native tau aggregation in the recipient neuron. In this review, we summarize the diverse cellular mechanisms associated with the secretion and uptake of tau, and highlight tau-trafficking receptors, which mediate tau clearance or cell-to-cell tau transmission.